Strategic Challenges for Russian-Turkish Relations An Analytical Study (Raparin Journal of Humanities (RJH), 2022)
Russian-Turkish relations are considered complex bilateral relations, extending over centuries, and having intertwined roots. Overlapping geopolitical regions and determinants that form hotbeds of conflict between the two states, global influences, and national and religious motives, all stand in the way of building normal relations between the two states. Nevertheless, the development of an intellectual structure and political and economic traditions of cooperation between the two states, towards unifying them under a Eurasian umbrella umbrella This remains elusive because of the different premises of each country towards the other.